Effects of co-overproduction of sedoheptulose-1, 7-bisphosphatase and Rubisco on photosynthesis in rice. Issue 1 (2nd January 2019) - Suzuki, Yuji; Wada, Shinya; Kondo, Eri; Yamori, Wataru; Makino, Amane
ABSTRACT: Overproduction of Rubisco did not proportionately increase the rate of CO2 assimilation ( A ) in rice probably because the capacity of regeneration of the substrate of Rubisco, ribulose-1, 5-bisphosphate (RuBP), could not afford the increased Rubisco capacity. Since sedoheptulose-1, 7-bisphosphatase (SBPase) is thought to be one of the limiting factors of RuBP regeneration capacity, SBPase and Rubisco were co-overproduced in rice in order to improve photosynthesis. Although SBPase and Rubisco contents increased by 82–102% and 20–30%, respectively, A did not increase under the conditions of high irradiance and different [CO2 ] partial pressures. Thus, co-overproduction of SBPase and Rubisco did not improve photosynthesis in rice. Overproduction and antisense suppression of SBPase did not greatly affect A at high [CO2 ], although it is thought to be determined by RuBP regeneration capacity. These results strongly suggest that SBPase does not determine RuBP regeneration capacity in rice. This is likely to be the reason for the unimproved photosynthesis by co-overproduction of SBPase and Rubisco.